Pulmonary nocardiosis in Western Europe—Clinical evaluation of 43 patients and population-based estimates of hospitalization rates. (April 2019) - Ott, Sebastian R.; Meier, N.; Kolditz, Martin; Bauer, Torsten T.; Rohde, Gernot; Presterl, Elisabeth; Schürmann, Dirk; Lepper, Philipp M.; Ringshausen, Felix C.; Flick, Holger; Leib, Stephen L.; Pletz, Mathias W.; et al.
Abstract: Background: Pulmonary nocardiosis (PN) is an uncommon but potentially life-threatening infection. Most of our knowledge on PN is derived from case reports and small case series. Increasing incidence rates of PN have been reported recently. The aim of this study was to describe the clinical course of and risk factors for PN in four Western European countries and to estimate population-based annual hospitalization rates. Methods: This was a retrospective evaluation (1995–2011) of the clinical course of and risk factors for PN in patients at 11 hospitals in four European countries (Germany, Austria, Switzerland, and the Netherlands). Population-based estimates of hospitalization rates for PN in Germany (2005 to 2011) were calculated using official German nationwide diagnosis-related groups (DRG) hospital statistics. Results: Forty-three patients fulfilled stringent criteria for proven ( n  = 8) and probable ( n  = 35) PN; seven had extrapulmonary dissemination. For these 43 patients, the major risk factors for PN were immunocompromising (83.7%) and/or pulmonary (58.1%; as only comorbidity in 27.9%) comorbidities. The median duration of PN targeted therapy was 12 weeks. Distinctive patterns of resistance were observed (imipenem susceptibility: Nocardia farcinica 33.3%; Nocardia asteroides 66.7%). The overall mortality rate was 18.9% (50% in disseminated PN). Over time, annual PN hospitalization rates remained unchanged at around 0.04/100 000, with the highest rate among men aged 75–84 years (0.24/100 000). Conclusions: PN is a rare, but potentially life-threatening disease, and mainly affects immunocompromised elderly males. Overall, annual hospitalization rates remained stable between 2005 and 2011.